Integrating Local Cultural Wisdom in Project-Based Learning to Improve Science Education: A Study of Kudus - Esty Cahyaningsih; Hermin Suprijati; Lim Azy (Al-Qalam Institue, 2024)
21st-century learning requires students to master the skills of 4C (critical thinking, creativity, communication, and collaboration). For this reason, teachers need to choose the right learning model to accommodate the needs and characteristics of students so that learning goals can be achieved optimally. This study aims to explore the implementation of the Project-Based Learning (PjBL) learning model contextualized with the local wisdom of Kudus culture in improving understanding of concepts and problem-solving skills in Madrasah Ibtidaiyah students. The approach used in this study is qualitative with a case study method. This research was conducted at Madrasah Ibtidaiyah, and the research subjects consisted of principals, teachers, and grade V students. Data was collected through interviews, observations, and documentation, then analyzed using interactive model data analysis techniques from Miles, Huberman, and Saldana, including the stages of data condensation, data presentation, and conclusion. The study results show that science learning using the PjBL model contextualized with the local wisdom of Kudus culture has a positive and practical impact in improving the understanding of concepts and problem-solving skills of Madrasah Ibtidaiyah students. The contribution of this research is to provide insight into the application of a project-based learning model that integrates local cultural values, which can be used as a reference in developing learning strategies that are more contextual and relevant to the needs of students in the era of globalization.